Implementing biofeedback treatment in a psychosomatic-psychotherapeutic inpatient unit: a mixed methods evaluation of acceptance, satisfaction, and feasibility - Schmidt, Kira; Barac-Dammeyer, Drazena; Kowalski, Axel; Teigelack, Per; Pfeiffer, Corinna; Robitzsch, Anita; Dörrie, Nora; Skoda, Eva-Maria; Bäuerle, Alexander; Fink, Madeleine; Teufel, Martin (Frontiers in Psychiatry, 2023)
Introduction: Feedback-based therapies such as biofeedback have a benefit in patients with mental health disorders. While biofeedback is heavily researched in outpatient settings, it has been rarely investigated in psychosomatic inpatient settings. The implementation of an additional treatment option in inpatient settings holds special requirements. The aim of this pilot study is the evaluation of additional biofeedback treatment in an inpatient psychosomatic-psychotherapeutic unit to derive clinical implications and recommendations for the future implementation of biofeedback offers. Methods: The evaluation of the implementation process was investigated using a convergent parallel mixed methods approach (following MMARS guidelines). Quantitative questionnaires measured patients’ acceptance and satisfaction with biofeedback treatment after receiving 10 sessions in addition to treatment as usual. After 6 months during implementation, qualitative interviews were conducted with biofeedback practitioners, i.e., staff nurses, examining acceptance and feasibility. Data analysis was conducted using either descriptive statistics or Mayring’s qualitative content analysis. Results: In total, 40 patients and 10 biofeedback practitioners were included. Quantitative questionnaires revealed high satisfaction and acceptance in patients regarding biofeedback treatment. Qualitative interviews showed high acceptance in biofeedback practitioners but revealed several challenges that were encountered during the implementation process, e.g., increased workload due to additional tasks, organizational and structural difficulties. However, biofeedback practitioners were enabled to expand their own competencies and take over a therapeutic part of the inpatient treatment. Discussion: Even though patient satisfaction and staff motivation are high, the implementation of biofeedback in an inpatient unit requires special actions to be taken. Not only should personnel resources be planned and available in advance of implementation but also be the workflow for biofeedback practitioners as easy and quality of biofeedback treatment as high as possible. Consequently, the implementation of a manualized biofeedback treatment should be considered. Nevertheless, more research needs to be done about suitable biofeedback protocols for this patient clientele.